Fireworks: A major source of inorganic and organic aerosols during Christmas and New Year in Mexico city - Retama, Armando; Neria-Hernández, Angélica; Jaimes-Palomera, Mónica; Rivera-Hernández, Olivia; Sánchez-Rodríguez, Miguel; López-Medina, Alfonso; Velasco, Erik (Atmospheric Environment: X, 2019)
The fireworks activity in Christmas and New Year is the culprit of a substantial increase in the particles pollution during those festivity dates in Mexico City. The fireworks' thrilling explosions fill the air with small particles full of metals and organic and inorganic species, and noxious gases such as sulfur dioxide, nitrogen dioxide, carbon monoxide and nitrous acid (HONO). The stagnant atmosphere at night accumulates the fireworks haze under a shallow boundary layer. By sunrise, once the fireworks activity has stopped, the photolysis of the abundant HONO accumulated throughout the night, leads to a rapid production of nitrate (NO3−), ammonium (NH4+), sulfate (SO42−) and low volatility secondary organic aerosols. This was the pattern observed during the winter of 2013–2014, when online measurements of water-soluble inorganic ions in particles smaller than 2.5 μm (PM2.5), non-refractory ions and organics in particles smaller than 1 μm (PM1), equivalent black carbon, and above-mentioned gases were conducted. The geometric average of the sum of the three major inorganic ions, NO3−, NH4+ and SO42− accounted for 25% (28%) and 34% (37%) of the total PM2.5 mass during the fireworks activity at night and the following morning on Christmas Day (New Year's Day), respectively. Similarly, their sum in the non-refractory fraction accounted for 37% (49%) and 47% (53%) of the total NR-PM1 mass concentration, while the organic fraction accounted for 56% (44%) and 49% (44%). Biomass burning organic aerosols and semi-volatile oxygenated organic aerosols (BBOA and SV-OOA, respectively) dominated the organic fraction during the fireworks period at night, while the low-volatility oxygenated organic aerosols (LV-OOA) increased substantially their concentration along the post-firework hours the following morning. Concentrations of PM2.5 > 100 μg m−3 and PM1 > 50 μg m−3 were observed on both days, with maximums of 157 and 137 μg m−3 for PM2.5 and PM1, respectively. The meteorological conditions helped to reduce the fireworks impact by late afternoon on both days, limiting the firework episodes to 22 h. The SO42− and NO3− related to the fireworks were not able to offset the deficit of NH4+, and thus the acidity nature of the particles during the mild winter of Mexico City did not change. Keywords: Fireworks, Pyrotechnics, Chemical composition, Water-soluble inorganic ions, Organic aerosols